2020
DOI: 10.1074/jbc.ra120.014999
|View full text |Cite
|
Sign up to set email alerts
|

The amphipathic helices of Arfrp1 and Arl14 are sufficient to determine subcellular localizations

Abstract: The subcellular localization of Arf family proteins is generally thought to be determined by their corresponding guanine nucleotide exchange factors (GEFs). By promoting GTP binding, GEFs induce conformational changes of Arf proteins exposing their N-terminal amphipathic helices, which then insert into the membranes to stabilize the membrane association process. Here, we found the N-terminal amphipathic motifs of the Golgi-localized Arf family protein, Arfrp1, and the endosome- and plasma membrane-localized Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…13 The ARL14 protein is involved in apoptosis signaling and several regulatory pathways. [25][26][27][28][29][30] Its homologous similar genes play an important role in human tumors; for example, ARF4 is involved in breast cancer cell migration as reported by Jang et al 31 Our study indicated that ARL14 protein appeared to be a promising candidate as a therapeutic target and prognostic predictor. Using bioinformatics analysis based on online datasets, survival analysis revealed the prognostic value of ARL14 in NSCLC.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…13 The ARL14 protein is involved in apoptosis signaling and several regulatory pathways. [25][26][27][28][29][30] Its homologous similar genes play an important role in human tumors; for example, ARF4 is involved in breast cancer cell migration as reported by Jang et al 31 Our study indicated that ARL14 protein appeared to be a promising candidate as a therapeutic target and prognostic predictor. Using bioinformatics analysis based on online datasets, survival analysis revealed the prognostic value of ARL14 in NSCLC.…”
Section: Discussionsupporting
confidence: 65%
“… 13 The ARL14 protein is involved in apoptosis signaling and several regulatory pathways. 25–30 Its homologous similar genes play an important role in human tumors; for example, ARF4 is involved in breast cancer cell migration as reported by Jang et al 31 …”
Section: Discussionmentioning
confidence: 92%
“…To test whether PRRC1 can be recruited to ERESs in a GTP-dependent manner, we performed a digitonin-permeabilized cell assay ( 35 ). HeLa cells were permeabilized, salt washed, and incubated with cytosol prepared from HEK293T cells expressing PRRC1-HA in the presence of GTP or GMPPNP.…”
Section: Resultsmentioning
confidence: 99%
“…Quantifications of the total fluorescence of Sec31A and Gogin97 were performed as described using ImageJ ( 46 ). Permeabilized cell assays were performed as described previously ( 35 ).…”
Section: Methodsmentioning
confidence: 99%
“…S2C). The deletion of the amphipathic helix J o u r n a l P r e -p r o o f of ARLs like ARFRP1and ARL14 or mutations in the myristoylation site of ARL5B and ARL1 was previously shown to have a similar localization (18,48,49).…”
Section: Discussionmentioning
confidence: 99%